PTSD and opioid use: implications for intervention and policy - Lucia Dahlby; Thomas Kerr (BMC, 2020)
Abstract Background North America remains in the midst of an escalating opioid overdose epidemic, largely driven by the influx of synthetic opioids such a fentanyl and related analogues. High rates of mental illness among substance-using populations have been well documented; in particular, opioid-using individuals suffer from high rates of PTSD. Despite the devastating disease burden of both PTSD and OUD, especially within the context of the current opioid overdose epidemic, treatment options and outcomes remain suboptimal. Main body Comorbid PTSD-OUD is often complex and inextricably intertwined, thereby impeding effective diagnosis, assessment and early intervention. Best outcomes occur when treatment addresses both comorbidities simultaneously, known as parallel or integrative approaches. Despite these findings, affected individuals often do not receive adequate or equitable access to healthcare. The WHO recommends that public spending for both mental and physical aspects of healthcare be equitable to the burden of disease. Despite these recommendations mental healthcare services remain chronically underfunded in Canada. The Mental Health Parity Act is a call for the Canadian government to implement equitable public spending on all aspects of healthcare. Furthermore, prohibitory legislative practices serve to marginalize substance-using populations thereby increasing the likelihood of exposure to traumatic violence and other associated harms. Conclusion Efforts are now needed to address regulatory drug-use frameworks and public healthcare policies that perpetuate these inequalities. Alternative regulatory frameworks for drugs and mental health parity should be implemented and evaluated in an effort to reduce violence, trauma and ultimately opioid-related overdose deaths.